Perspectives for research of the procrastination phenomenon in professional work - Valentina V. Barabanshchikova; Galina I. Marusanova (Национальный психологический журнал, 2015)
The paper describes the current state of the procrastination phenomenon in professional work, reviews the basic unexplored aspects in this area, and highlights the promising areas of scientific analysis. The survey of the existing literature periodization shows that the quantity of researches devoted to procrastination is growing exponentially every year. In spite of a pronounced research interest in this construct, in native and foreign psychological science procrastination phenomenon in the professional work is represented insufficiently. Firstly, there is no common and generally accepted definition of procrastination (Corkin, Yu, Lindt, 2011; Steel, 2010; Krause, Freund, 2014), that suggests that there is a deep terminological crisis in this area. Secondly, the characteristic of delaying the implementation of the elements of workload is represented only by the example of a fairly narrow range of professional activities, which makes it relevant to study the specificity of the differentiated functioning of the phenomenon on the material of a wide range of professions. Thirdly, in psychology there are no information about the peculiarities of the so-called “active” procrastination manifestations in professional activity, which is the tendency of conscious assignments delaying to achieve the optimum final result (Chu, Choi, 2005; Choi, Moran, 2009). Fourthly, there is an acute shortage of standardized psychodiagnostic tools to evaluate this phenomenon in work (most of the existing methods have been tested on samples of students and are aimed at identifying academic procrastination). In the fifth place, there are no science-based allocation of methods of coping with destructive manifestations of the psychological strategy of the job functions postponement in a professional work.